Pengaruh disiplin kerja, kompetensi, dan motivasi instrinsik pada saat pandemi covid-19 terhadap resiliensi kinerja karyawan di Industri Sembung Batik Kulon Progo - Prayekti, Prayekti; Maulida Kurniati, Fakhmi (Jurnal Paradigma Ekonomika, 2024)
This observation aims to determine (1) the effect of work discipline on performance resilience, (2) competence on performance resilience, and (3) intrinsic motivation on performance resilience, (4) work discipline, competence, and intrinsic motivation on performance resilience. The sampling technique used is non-probability sampling with saturated sampling technique (census). The results of these observations show that (1) positive and significant influence of work discipline on resilience performance of the Sembung Batik Kulon Progo Industry Employees. (2) the non-significant effect of competence on performance resilience in Sembung Batik Kulon Progo Industry Employees. (3) the positive and significant effect of intrinsic motivation on performance resilience in the Sembung Batik Kulon Progo Industry Employees. (4) the positive and significant influence of work discipline, competence and intrinsic motivation on the resilience of the performance of the employees of the Sembung Batik Kulon Progo Industry.